Bacterial Agent Transfer from Inanimate Objects of Healthcare Personnel to Patients in Operating Theatres and ICUS at A Tertiary Care Hospital in Visakhapatnam, India - Dr. Krishna Agarwal,; Dr. Sandeep Saraf, (International Journal of Pharma and Bio Sciences, 2024)
This research focuses on the critical concern of cross-contamination of bacterial agents in healthcare settings, particularly the transmission from inanimate objects utilized by health personnel to patients within operation theatres and intensive care units (ICUs) at a prominent Tertiary care hospital situated in Visakhapatnam, India. The primary objective of this study is to comprehensively investigate and analyze the scope and implications of this cross-contamination phenomenon. Understanding the pathways through which bacterial agents are transferred is paramount in the context of rising healthcare-associated infections. This study explores the extent of such transmission events, elucidating the potential risks posed to patients with compromised immune systems in high-risk areas such as operation theatres and ICUs. The research endeavors to achieve several specific objectives: identifying prevalent bacterial species on inanimate objects and surfaces, quantifying the frequency of crosscontamination incidents, evaluating the adherence of healthcare personnel to established hygiene protocols, and assessing the effectiveness of current disinfection practices. Through rigorous data collection and analysis, this study aspires to contribute vital insights into bacterial transmission and contamination dynamics in healthcare environments. The findings of this research are expected to guide the enhancement of infection control strategies, facilitate the implementation of targeted interventions, and ultimately mitigate the risks associated with cross-contamination. By improving hygiene practices and bolstering patient safety protocols, the study aims to reinforce the overall quality of healthcare delivery in the hospital setting, thereby safeguarding the health and well-being of patients and promoting excellence in medical care standards.